MANAJEMEN PONDOK PESANTREN BAITUL AKBAR DALAM MEMBENTUK SIKAP DISIPLIN SANTRI - puspitasari, niken siti; Chofshoh, Umi; Tyas, Zuhriana Widya Rahayu Ning (Institut Agama Islam Ngawi, 2024)
Nowadays, many students have behavior that is inappropriate and even contrary to moral attitudes, thus hindering the learning process. The attitudes of students, such as brawling, smoking drugs, not doing homework, even fighting with teachers and fighting with classmates, are all stemming from individuals who lack discipline. The aim of this research is to describe the planning, implementation, supervision and methods applied in forming students' disciplinary attitudes. This research uses a qualitative approach and a case study type approach. The results of this research are at the planning stage, namely by forming student management and regulations, at the implementation stage, namely the boarding school manager provides direction and punishment for students who deviate, at the monitoring stage, namely by holding evaluation deliberations. Meanwhile, the methods used are supervision, ta'zir system and punishment.